Exo-pectinase production by Bacillus pumilus using different agricultural wastes and optimizing of medium components using response surface methodology - Tepe, Ozlem; Dursun, Arzu Y. (Springer Heidelberg, 2014)
In this research, the production of exo-pectinase by Bacillus pumilus using different agricultural wastes was studied. Agricultural wastes containing pectin such as wheat bran, sugar beet pulp, sunflower plate, orange peel, banana peel, apple pomace and grape pomace were tested as substrates, and activity of exo-pectinase was determined only in the mediums containing sugar beet pulp and wheat bran. Then, effects of parameters such as concentrations of solid substrate (wheat bran and sugar beet pulp) (A), ammonium sulphate (B) and yeast extract (C) on the production of exo-pectinase were investigated by response surface methodology. First, wheat bran was used as solid substrate, and it was determined that exo-pectinase activity increased when relatively low concentrations of ammonium sulphate (0.12-0.21 % w/v) and yeast extract (0.12-0.3 % w/v) and relatively high wheat bran (5-6 % w/v) were used. Then, exo-pectinase production was optimized by response surface methodology using sugar beet pulp as a solid substrate. In comparison to P values of the coefficients, values of not greater than 0.05 of A and B (2) showed that the effect of these process variables in exo-pectinase production was important and that changes done in these variables will alter the enzyme activity.
Keywords: Agricultural wastes; Bacillus pumilus; Exo-pectinase; Response surface methodology; Solid-state fermentation